Commercial bioinoculants improve colonization but do not alter the arbuscular mycorrhizal fungal community of greenhouse-grown grapevine roots - Mariam P. Berdeja; Nicole K. Reynolds; Teresa Pawlowska; Justine E. Vanden Heuvel (Environmental Microbiome)
Abstract Background Arbuscular mycorrhizal fungi (AMF) are beneficial root symbionts contributing to improved plant growth and development and resistance to abiotic and biotic stresses. Commercial bioinoculants containing AMF are widely considered as an alternative to agrochemicals in vineyards. However, their effects on grapevine plants grown in soil containing native communities of AMF are still poorly understood. In a greenhouse experiment, we evaluated the influence of five different bioinoculants on the composition of native AMF communities of young Cabernet Sauvignon vines grown in a non-sterile soil. Root colonization, leaf nitrogen concentration, plant biomass and root morphology were assessed, and AMF communities of inoculated and non-inoculated grapevine roots were profiled using high-throughput sequencing. Results Contrary to our predictions, no differences in the microbiome of plants exposed to native AMF communities versus commercial AMF bioinoculants + native AMF communities were detected in roots. However, inoculation induced positive changes in root traits as well as increased AMF colonization, plant biomass, and leaf nitrogen. Most of these desirable functional traits were positively correlated with the relative abundance of operational taxonomic units identified as Glomus, Rhizophagus and Claroideoglomus genera. Conclusion These results suggest synergistic interactions between commercial AMF bioinoculants and native AMF communities of roots to promote grapevine growth. Long-term studies with further genomics, metabolomics and physiological research are needed to provide a deeper understanding of the symbiotic interaction among grapevine roots, bioinoculants and natural AMF communities and their role to promote plant adaptation to current environmental concerns.